Phenolic Compounds in Selected Oats and Rice Products - Hossain, Zakir (My University, 2024)
Oats and rice are nutritious gluten-free foods and food ingredients. The phenolic compounds of these sustainable cereals have been primarily studied in their natural form, although food processing is known to affect the phenolic compounds. This study identified and quantified the phenolic acids and avenanthramides of selected oat and rice products used in the Oat Gut Brain (OGB) research project. OGB is a clinical trial that studied the health effects of oat and rice product-based diets. All the sample sets were prepared as provided in the clinical trial. The samples were extracted with 80% methanol and analysed using high-performance liquid chromatography with diode-array detection (HPLC-DAD). Eight phenolic acids and five avenanthramides were identified- Avenanthramides were only present in oat-based products. The most abundant phenolic acids in oat and rice samples were p-coumaric and ferulic acids. In oat-based samples, total phenolic-acids content (TPC) was 1.59 – 404.38 mg/100 g of dry weight (dew) samples, and total avenanthramides content (TAC) was 0.68 – 12.23 mg/100 g (dw). In comparison, rice-based samples provided 2.33 – 82.01 mg of TPC in 100 g (dw). Oat muesli contained the highest amount of TPC and TAC, possibly due to flavouring agents in it. There were strong relationships between the phenolic contents and nutritional composition of the samples, and the samples were significantly different from each other (p<0.05). In conclusion, more phenolic compounds were quantified in oat-based samples than in rice samples, even after processing. A more significant number of phenolic compounds were identified in oat samples. Not only oats or rice but also the flavouring agents were estimated to affect the results of some products.
Keywords: avenanthramides, HPLC-DAD, oat, rice, PCA, total phenolic content